2012
DOI: 10.1590/s0102-86502012000100001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zafirlukast on capsular contracture around silicone implants in rats

Abstract: PURPOSE:To evaluate the effect of zafirlukast on capsular contracture around silicone implants by measuring the pressure within the implant, using a rat experimental model. METHODS: Forty adult female Wistar rats were used. Each one received two silicone implants, one with smooth-surface and the other with textured-surface. They were randomly divided into four groups (n=10). The rats of control group I were sacrificed after the implants. The remaining animals were subjected to a daily regimen of intra-peritone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
1
8
0
2
Order By: Relevance
“…The leukotriene antagonist, Zafirlukast (AstroZeneca) has been used off label to investigate whether it has an effect on the development of contracture. Animal studies have found that when 5 mg/kg per day of Zafirlukast was injected around textured silicone implants, the capsules are thinner and more vascular with a lower collagen density [ 75 76 ], indicating that the drug may be able to prevent capsular contracture from developing in the first place. A number of studies have also been carried out in women who have undergone implant based surgery.…”
Section: Management and Prevention Of Capsular Contracture: New Stratmentioning
confidence: 99%
“…The leukotriene antagonist, Zafirlukast (AstroZeneca) has been used off label to investigate whether it has an effect on the development of contracture. Animal studies have found that when 5 mg/kg per day of Zafirlukast was injected around textured silicone implants, the capsules are thinner and more vascular with a lower collagen density [ 75 76 ], indicating that the drug may be able to prevent capsular contracture from developing in the first place. A number of studies have also been carried out in women who have undergone implant based surgery.…”
Section: Management and Prevention Of Capsular Contracture: New Stratmentioning
confidence: 99%
“…Animal studies revealed that when 5 mg/kg leukotriene antagonist zarlukast is injected daily around the rough silicone rubber material, the capsule around the silicone rubber is thinner, the vascularization of the capsule is more abundant, and the collagen density is lower, indicating that this drug can prevent capsule contracture ( Hinz et al, 2001 ; Mazzocchi et al, 2012 ). A study involving 60 patients with mild and severe capsular contracture evaluated monthly up to a year after the initiation of a 6-months treatment with zarlukast revealed that during active treatment, the Baker score of the contracture decreased, after the patient stopped treatment, the score began to increase ( Bastos et al, 2012 ). This result suggests that to obtain long-term effects, long-term treatment is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…18 There are numerous theories regarding the cause of capsular contracture, such as implant-related factors, different implant insertion planes, foreign body reaction, hematoma, bacterial contamination, and subclinical infection. 4,19,20 Despite various hypotheses, capsular contracture formation is accepted to be multifactorial having inflammation as a common denominator. 6,21 Systemic and local response of the body to implants is still being debated, and increasing biocompatibility is an area of ongoing research.…”
Section: Discussionmentioning
confidence: 99%